Pemupukan Berimbang Spesifik Lokasi Melalui Evaluasi Kesuburan Tanah di Lahan Sawah Kecamatan Selemadeg Timur - Reni, I Luh; Kartini, Ni Luh; Trigunasih, Ni Made (Agrotrop : Journal on Agriculture Science; Vol 15 No 1 (2025), 2025)
Location-Specific Balanced Fertilization for Enhancing Rice Productivity in East Selemadeg District. Rice, the backbone of Indonesian agriculture, faces persistent productivity challenges, with fertilization emerging as a critical bottleneck. This study endeavors to gauge soil fertility, chart its spatial distribution, and furnish precise, site-specific fertilizer recommendations for rice fields in East Selemadeg District. Employing survey methodologies coupled with rigorous soil testing in laboratory settings, we unveil two distinct soil fertility classifications prevailing across the research area. Notably, SLH VI emerges as a beacon of high fertility, encompassing regions like Mount Salak and Dalang. Conversely, varying degrees of medium fertility characterize SLH I, II, III, IV, V, and VII, spanning different locales within the district. Our findings underscore the imperative for tailored interventions to optimize rice cultivation practices. Furthermore, our analysis identifies low C-organic and K-total content as pivotal limiting factors in soil fertility. To address these deficiencies, we advocate for the incorporation of organic fertilizers alongside a targeted application of 100 kg/ha of KCI. This research not only elucidates the intricate nuances of soil fertility dynamics but also lays the groundwork for precision-driven fertilization strategies, poised to elevate rice yields and foster agricultural sustainability in the region.